Persistent perineal sinus following proctocolectomy in the inflammatory bowel disease patient - Sam D. Papasotiriou; Gregory A. Dumanian; Scott A. Strong; Stephen B. Hanauer (JGH Open, 2023)
Abstract Prolonged perineal wound healing following proctocolectomy in patients with inflammatory bowel disease (IBD) is a frustrating result for the medical team and patients who were hoping for improved quality of life. Prolonged healing, which lasts more than 6 months following proctocolectomy, is termed persistent perineal sinus (PPS) and typically necessitates further surgical management. Healing of the PPS is difficult due to the resulting “dead space” following proctocolectomy, necessitating the need to fill the void with viable tissue in an area with anatomic constraints. Here we provide a narrative review and comprehensively address the incidence, pathogenesis, and clinical and operative management of a PPS in patients with IBD following proctocolectomy. Operative methods discussed include surgical debridement, flap closure of the perineum, omental flap closure, and gracilis muscle transposition. It is necessary to further investigate and establish a gold standard of care for these patients.